THE EFFECT OF GRANDCHILD CARE ON SPOUSAL RELATIONSHIP SATISFACTION OF GRANDPARENTS: A COARSENED EXACT MATCHING. (11th November 2018) - Park, H; Jun, H; Joo, S
Abstract: As grandparents' participation in grandchild care increases, studies on the effects of grandchild care on grandparents have been actively conducted worldwide. However, only a few studies have examined the effects of grandchild care on grandparent's relationship with a spouse, which is considered to be the most important social relationship in later life. Therefore, this study is conducted to investigate the effect of grandchild care on spousal relationship satisfaction of grandparents aged 53 and older who have at least one grandchild and a spouse (N=3, 774). For the analysis, the 5th wave of the Korean Longitudinal Study of Ageing was utilized. Spousal relationship satisfaction, the dependent variable, was measured by a single question and participation in grandchild care, the independent variable, was measured as a dummy variable. Age, gender, educational level, employment status, household income, and subjective health were included as control variables as well as matching variables. To prevent selection bias, weighted regression analysis was performed on a sample matched through Coarsened Exact Matching (CEM), a matching method to adjust the imbalance between treatment and comparison groups. The findings showed that grandchild care had a significant effect on spousal relationship satisfaction of the grandparents; grandparents who participated in grandchild care were more satisfied with the relationship with their spouses (b=3.98, p<.05). This study may be meaningful in that it empirically explores the net effect of grandchild care on spousal relationship satisfaction of grandparents using CEM with nationwide data, and presents a new model of marriage in later life.